APPLICATION OF MIRROR THERAPY IN PATIENTS WITH STROKE - Mariela Filipova; Elka Goranova; Daniela Popova (Peytchinski Publishing, 2023)
Purpose. The aim of the study was to investigate the effect of mirror therapy as a method of restoring damaged upper limb function in patients with ischemic stroke treated with venous thrombolysis. Materials. Mirror therapy was administered to 10 thrombolyzed patients with ischemic stroke. The patients were treated in the neurological ward of the Multi-profile Hospital for Active Treatment-Blagoevgrad in the period from 2014-2015. After signing a declaration of informed consent of the patients, a Barthel index test was applied before and after hospitalization. The duration of the procedure is 15-20 minutes for 5 days and is part of the general kinesitherapy program. The Prizm statistical package was used for statistical data processing and graphical presentation. Results. The mean age of the studied contingent was 67±2.8 years. Our new and specialized method of kinesitherapy for the recovery of patients treated with venous thrombolysis confirms a significant positive effect (Wilcoxon, ANOVA). Conclusion. The results of our research show that the application of the author's methodology with mirror therapy creates an opportunity to improve the functions in the damaged upper limb and improves the quality of life.